Analisis Pengelolaan Obat Dan Strategi Perbaikan Dengan Metode Hanlon Di Instalasi Farmasi RSU Budi Setia Kabupaten Minahasa Provinsi Sulawesi Utara - Hanna Mariana Rumagit; Titik Sunarni; Ika Purwidyaningrum (Fakultas Farmasi Universitas Setia Budi, 2024)
Pharmaceutical installation is a part in the hospital responsible carry out the management of a drug that covers the, selection , procurement distribution and use of medicine.The problem of managing a drug can affect the availability of medicines. This study aims to analyse the efficiency of drug management in IFRSU Budi Setia Minahasa regency. The study design was descriptive for the data that is retrospective and concurrent. Data obtained from IFRSU Budi Setia stage drug management in, analyzed the efficiency of using indicators, then compared to the standard or the results of other studies. The results show the results not according to standards: Selection, compliance with Fornas (65,28%), procurement, allocation of available funds (14,74%), the frequency of each item procurement of drugs (6,02 times a year), and EOQ (8,16 times/year), the distribution, the medicinal value of the damaged/expired (1,16%), the stock is dead (0,6%), the use, the number of items per strip of prescription drugs (3,22 sheet). The results according to the standard are: procurement, capital funds available to the overall funds needed (100%), incomplete SP/Invoices (0 times), the number of drug items held as planned (100%), the distribution, the accuracy of the amount of drug on card stock (100%), TOR (12,28 times), the rate of drug availability (12 months), stage of use, the number of items cents ( 3,22 ) prescription drugs, prescribing generic name (90,25%), the average time spent on prescriptions of non concoction (2,8 min) compounded prescription (3,5 minutes). Priority problem handling method hanlon: (1) percentage of stock dead, (2) percentage of and medicinal value expired and or damaged, (3) the number of items cents a prescription drug, (4) conformity items a drug that is available with fornas, (5) the frequency of procurement every items drug per year, (6) allocation percentage funds procurement drug 2019.